Diode-End-Pumped Continuous-Wave Tunable Nd3+:LiYF4 Laser Operating on the 4F3/2→4I13/2 Transition - Chu Chu; Shuang Wang; Xinhua Fu; Zhenhua Du (Photonics)
A laser diode (LD) end-pumped continuous-wave (CW) tunable Nd3+:LiYF4 (Nd:YLF) laser operating on the 4F3/2→4I13/2 transition was performed. Four single-wavelength (SW) lasing at 1321, 1314, 1371, and 1364 nm in the π-polarized direction and three SW lasing at 1314, 1326, and 1371 nm in the σ-polarized direction were achieved using a tuning prism. At 20 W pump power, the σ-polarized 1314 nm emission generated 7.3 W power output with 39.4% slope efficiency. Further, the three-pair of switchable π-polarized dual-wavelengths (DWs) at 1321/1314 nm, 1371/1364 nm, and 1321/1364 nm and the two-pair of switchable σ-polarized DWs at 1314/1326 nm and 1314/1371 nm were also realized by rotating an intracavity birefringence filter (BF). In addition, by employing dual intracavity BFs, the balanced DW output power was attained, achieving 6.4 W total maximum output at 1314/1321 nm in the π-polarized direction.